PENDEKATAN TASAWUF DALAM KAJIAN SHOLAT - Wildan Setiawan; Mohamad Zaenal Arifin (Ma'had Aly Journal of Islamic Studies, 2026)
This paper discusses the Sufi approach to prayer (ṣalah) as an effort to understand Islamic worship not merely from its outward legal dimension (fiqh), but also from its inner and spiritual aspects. This study employs a qualitative method through library research, drawing upon classical and contemporary books, academic journals, and relevant online sources. The discussion focuses on the definition of Sufism and prayer, the characteristics of the Sufi approach, the function of Sufism in religious life, and the perspectives of prominent Sufi figures—particularly Imam al-Ghazali and Ibn ‘Aṭa’illah al-Sakandari—regarding prayer. The findings indicate that Sufism views prayer as a means of purifying the soul, a medium for intimate supplication, and a path toward spiritual closeness to Allah. The Sufi approach emphasizes the presence of the heart, understanding the meanings of the recitations, and internalizing the spiritual values of prayer. Therefore, the integration of sharia and Sufism is essential to realizing prayer that is not only legally valid but also spiritually meaningful.